Perspectives on learning to practice reflexivity while engaging communities in implementation science - Woodward, Eva N.; Ball, Irenia A. (Frontiers in Health Services, 2023)
Background: As implementation scientists and practitioners engage community members and service users, reflexivity rises as a critical approach for managing power imbalances and effective collaborative work to promote equity. Reflexivity is an approach for acknowledging scientists’ own positions, including their understanding and limits of how they view their phenomena of inquiry. We describe our perspective practicing reflexivity as an implementation science team new to community engagement. Methods: We spent over two years learning principles of Community-Based Participatory Research (CBPR) to inform implementation science and practice, then applied CPBR principles into a new community-academic partnership in August 2020 for and with veterans of the United States Military living in rural Arkansas. We used five methods to practice reflexivity for the first time: identifying positionality, writing fieldnotes, obtaining mentorship on technical aspects, comparing head notes, and consulting reference materials. Discussion: We found multiple methods for practicing reflexivity to be feasible, although difficult to stay consistent with busy schedules. Fieldnotes especially required commitment and were important not to minimize. Written fieldnotes enabled us to reflect on successes and missteps, funneling into action planning. Head notes allowed emotional catharsis and to generate insights based on each other’s perspectives. Referencing books or course modules reminded us of ideal CBPR principles. Discussion with mentors helped us with technical aspects and balancing real-world challenges with ideal CBPR principles. Our methods to practice reflexivity were valuable and directly impacted process and research outcomes. Future training for implementation science and practice might consider reflexivity practice as a core competency.